6th international scientific conference on defensive technologies OTEH 2014 (proceedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The article presents the basic information about the overal results, significance, international programme committee and working areas of the 6th International Scientific Conference on Defensive Technologies, OTEH 2014, in comparison with previous five conferences. The number of sections, number of papers, number of authors/coauthors, number of sessions and number of members of the scientific commitee are presented in the review. This year conference is the best regarding the number of papers and the number of authors/coauthors since this conference got its international character.